PEMBERDAYAAN MASYARAKAT MELALUI PENDEKATAN SOCIETY ACTION RESEARCH DALAM MENINGKATKAN KEMANDIRIAN EKONOMI LOKAL - Ahya Lailah Tasbihah; Dia Nada Kriswahyuni; Rahayu, Novi; Sofiyatun; Hana, Rissiril; Nur Laili Dina Hafni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Community empowerment has become a strategic approach to achieving sustainable local economic development by encouraging active community participation in the development process. However, many local communities still face challenges such as limited human resource capacity, inadequate access to capital, low innovation, and weak institutional support, resulting in low levels of economic independence. This study aims to analyze the implementation of the Society Action Research (SAR) approach in improving local economic independence through community empowerment. The research employed a qualitative approach using a library research method by reviewing books, scientific journals, government reports, and other relevant literature concerning community empowerment, participatory action research, and local economic development. The collected data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings indicate that the Society Action Research approach effectively strengthens community participation in identifying local problems, planning development programs, implementing community-based economic activities, and conducting participatory evaluation. Furthermore, this approach contributes to improving entrepreneurial skills, strengthening local economic institutions, expanding market access, and increasing community self-reliance through collaborative and sustainable development processes. Therefore, Society Action Research can serve as an effective model for promoting sustainable local economic empowerment by integrating research activities with practical community actions.